A Study on Culture and Starting of Buddhism Arts: Bridging differences in Buddhist traditions (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The teachings given by Siddhartha Gautama at the Deer Park at Varanasi, India 2500years ago have now spread worldwide, resulting in a rich tapestry of traditionswhich can seem quite confusing. Buddhism is a peace loving, compassionate spiritualpath, so to bridge differences between its various traditions and to worktogether, representatives from all Buddhist schools convened at the WorldBuddhist Sangha Council, Sri Lanka 1966 and unanimously reached agreementthat: